The Effects of Sulphuric Acid and Sodium Chloride Agglomeration and Curing on Chalcopyrite Leaching - Víctor Quezada; Antoni Roca; Oscar Benavente; Montserrat Cruells; Evelyn Melo (Metals, 2021)
An option to improve the leaching efficiency of chalcopyrite is pretreatment prior to leaching. Pretreatment variables, such as the curing time and the addition of chloride, can increase the kinetics of copper extraction, particularly for sulphide ores. However, there has been little research on the topic. The reactions that govern this phenomenon have not been clearly identified. In this study, the effects of sulphuric acid and sodium chloride agglomeration and curing on chalcopyrite leaching were evaluated at various temperatures: 25, 50, 70, and 90 °C. The pretreated ore and leach residues were characterised by X-ray diffraction, scanning electron microscopy, and reflected light microscopy. Under the conditions of 15 kg/t of H2SO4, 25 kg/t of NaCl, and 15 days of curing time (as pretreatment), the following products were identified: CuSO4, NaFe3(SO4)2(OH)6, Cu2Cl(OH), and S0. Increasing the curing time and leaching temperature increased copper leaching. The copper extraction was 94% when leaching at 90 °C after pretreatment with 50 g/L of Cl− and 0.2 M of H2SO4. Elemental sulphur, jarosite, and copper polysulphide (CuS2) were detected in the leaching residues.